Age, growth and reproduction of the Axilary Seabream, "Pagellus acarne" (Risso, 1827), from the South coast of Portugal - Coelho, Rui (2005)
Axillary seabream, Pagellus acarne, caught by longlines in the Algarve (Southern Portugal), were sampled between August 1995 and August 1996. Age was studied by counting growth increments on otoliths and the estimated von Bertalanffy parameters were Linf = 28.82 cm, K = 0.29 year-1 and t0 = -1.47 year for males and Linf = 32.30 cm, K = 0.18 year-1 and t0 = -2.56 year for females. Evidence of the annual periodicity of the deposition of increments was found by marginal increment analyses. Macroscopic analysis of the gonads and the gonad somatic index showed that reproduction occurred over an extensive period of time, from May to November. Lengths at first maturity were 18.10 and 17.60 cm for males and females, respectively. This species was characterized as being a protandric hermaphrodite.